Single station bias calculation using data from calibrated GNSS station for various baseline distances - Shaikh, Muhammad Mubasshir (Progress in earth and planetary science, 2023)
Precise ionospheric TEC can be derived from dual-frequency GNSS carrier phase leveled pseudorange measurements. However, differential code biases (DCB) of satellite and receiver are the main errors that cannot be ignored for precise TEC calculation. We have proposed a method of calculating station DCB using calibrated STEC data from a baseline GNSS station. The method is simply based on the understanding that the ionosphere observed by two baseline GNSS stations at the same universal time (UT) can be considered similar and would pose similar delay to the signals propagating to the two stations. The method is tested for different baseline distances of 250–1000 km and in different latitudinal regions. For 500 km baseline, the average DCB calculation error for one year data is less than 0.22 ns, 0.11 ns, and 0.25 ns for low, mid and high latitude regions, respectively. The most consistent results were obtained from high latitudes where the standard deviation remains less than 0.22 ns. The least accurate were the low latitude results where the spread of error were between 0.29 to 0.50 ns. Results showed that the accuracy and consistency of the DCB estimation reduced with the increasing baseline distance between the two participating GNSS stations. This was specifically true for low latitude regions.